Beef production and environmental externalities in Nicaragua (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2017)
The present paper exposes the partial results of the research "Externalities, environment and economic policy in Nicaragua". The research is part of the Doctoral Program in Economic Sciences of the Faculty of Economic and Social Sciences of the Universidad del Zulia (Bolivarian Republic of Venezuela, 2011-2016), which consisted in determining the possible relationship between the associated market externalities and the Nicaragua's four main export headings, their impacts on the environment and potential risks to emerging economic activities. Results revealed that the agroexport model, in addition to generating large negative externalities, has been strengthened accompany by severe adverse environmental impacts. In the particular case of traditional beef production, due to the strong expansion of this item, stimulated by FOB export prices, it has become a major determinant of deforestation and a major source of methane emissions, one of the most potent greenhouse gases (GHGs) that affect global climate change attributable to anthropogenic causes.
Keywords: Beef; externalities; environmental impact; FOB prices; methane; Nicaragua